Coinfection of Plasmodium vivax and Epstein-Barr virus: case report - Akin, Fatih (Asian Pacific Tropical Medicine Press, 2013)
Malaria is an acute and chronic illness characterized by paroxysms of fever, chills, sweats, fatigue, anemia, and splenomegaly. It is still an important health problem in malaria-endemic countries. Children living in malaria-endemic areas have elevated Epstein-Barr Virus (EBV) loads in the circulation and acute malaria infection leads to increased levels of circulating EBV that are cleared after anti-malaria treatment. There are many reports about the association of Plasmodium falciparum (P. falciparum) malaria and EBV infection. Here we report a case who had coinfection of Plasmodium vivax (P. vivax) malaria and EBV infection. To the best of our knowledge this is the first case indicating the association of P. vivax malaria and EBV infection.